THE CORRELATION BETWEEN EXCLUSIVE BREASTFEEDING AND STUNTING IN CHILDREN UNDER FIVE IN MONTASIK, THE REGENCY OF ACEH BESAR IN 2025 - Oktaviani, Desi; Berkat, Satrinawati; Seriana, Irma (Department of Midwifery, Health Polytechnic of Aceh, 2025)
Background: Stunting is a chronic nutritional problem that affects children’s physical growth, cognitive development, health, and long-term productivity. In the working area of Montasik Health Center, Aceh Besar, the prevalence of stunting remains relatively high. One of the critical factors associated with stunting is exclusive breastfeeding. The objective of this study was to analyze the correlation between exclusive breastfeeding and stunting in children under five in Montasik, the regency of Aceh Besar in 2025 Subjects and Method: This study employed a quantitative, cross-sectional design. A total of 90 mothers with children under five years old were selected using proportional random sampling from several villages in Montasik Sub-district. Data were collected using questionnaires on exclusive breastfeeding practices and child nutritional status, and analyzed using the Chi-Square test to assess associations between variables. Results: The findings revealed a significant association between exclusive breastfeeding and stunting among children under five (p=0.000). Children who were not exclusively breastfed had a higher risk of stunting compared to those who received exclusive breastfeeding. Conclusion: Exclusive breastfeeding was significantly associated with stunting among children in Montasik Sub-district. Continuous health education and strong support from both families and health workers are essential to improve exclusive breastfeeding practices and reduce the prevalence of stunting.